Wheat Paste Di Jalanan Yogyakarta (Seni Cetak Grafis Sebagai Alternatif Media Pop Propaganda) - Rahman, Deni (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2013)
When we observe the Indonesian public space, in big cities such as Jakarta, Bandung and Yogyakarta, we can see that the space is now packed with a wide range of consumer imagery, which is offered by the owners of capital, with posters, banners, and billboards . Moreover we can found also the spirit of ‘youth rebellion’ through graffiti, murals, and which is now becoming more popular or well is a wheat paste. Competing for attention with the visual images in the public space, of course, will always be won by those who have capital. The street artist should be smart to choose the media and what is the most appropriate technique to use. Using printmaking with many variety of technical work to make wheat paste of popular propaganda, will be one of smart strategy, because printmaking can be created massive, but still has the artistic power. Keywords: propaganda, printmaking, street art, wheat paste